The Competence and Performance of Indonesian Vocational School Teachers Based on Professional Certification - Kadan Richard; Radna Andi Wibowo; Heri Prabowo; Soedjono (Journal of Education in Specific Purpose, 2025)
The teacher's role is very decisive in quality improvement efforts education. For this reason, teachers as learning agents are required to carry out the learning process as well as possible within the framework of educational development. The specific objectives of this study were to analyze the effect of competence on vocational high school teacher performance, both those who have followed professional certification and those who have not followed professional certification. First, descriptive statistics using the average score describe respondents' perceptions of teacher perfor-mance and teacher competence. Second, inferential statistics using regression analysis are used to test hypotheses. Finally, the t-test is used to analyze the difference between teacher competence and the performance of teachers who have not followed professional certification and those who have followed professional certification. The result is that competence influences teacher performance, which means the better the teacher's competence, the better the teacher's performance.